Dividend Puzzle on Bulgarian Stock Exchange - Opportunity for an Abnormal Risk-adjusted Returns - Pavlov, Ts.L. (Економічний вісник Донбасу, 2014)
The present paper examines the gap between the leading theoretical formulations about the optimal dividend policy and empirical data on the companies and investor’s behaviour known in the academic literature as “dividend puzzle”. The existence of this phenomenon and its impact on share prices are explored. The aim of the study is to establish whether it is possible risk-adapted high-yield to be realized through dividend investing. Empirical results show that the yield on the actively or passively managed portfolio of high-dividend-yield shares outperforms the main index of Bulgarian Stock Exchange -Sofia.